ESTRATEGIAS DE COMERCIALIZACIÓN Y SU INFLUENCIA EN EL NIVEL DE RENTABILIDAD DE TELEVENTAS DEL GRUPO UNICOMER ZONA 5. AUTORA: - Diaz Montenegro, Givana Andrea (2018)
he comments mentioned in the present research project, is original and exclusive responsibility of its author, prior to obtaining the title of commercial engineering, whose theme is Marketing Strategies and its influence on the level of profitability of Telemarketing of the Unicomer Group Zone 5, in such virtue I leave sample of this document as a result of inquiry, for which it exempts future commitments in the event of any consequence, responsibility for contents, ideas, analysis, conclusions, recommendations, proposals of this project of investigation correspondnexclusively and the intellectual heritage of the same to the Faculty of Administration, Finance and Informatics of the Technical University of Babahoyo